2019
DOI: 10.3844/ajbbsp.2019.138.149
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, Characterization and Antioxidant Activities of Selenized Polysaccharides from Hypsizygus marmoreus

Abstract: In this study, hypsizygus marmoreus was used as raw material to extract polysaccharides by hot water extraction method. Preparation technology of Selenized Polysaccharides from Hypsizygus marmoreus (SPHM) and its antioxidant activities were investigated. Chelation rate was selected as the index, effects of initial concentration of sodium selenite (mg/mL), the mass ratio of polysaccharide to sodium selenite, chelation time and pH on the chelation rate was investigated by single factor test. Response surface met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…PEP showed anti-inflammatory activity in RAW 264.7 macrophages, inhibiting pro-inflammatory mediators’ production and inhibiting inducible nitric oxide synthase expression, showing its potency for anti-inflammatory activity in the colon [ 315 ]. Liu et al reported the action of polysaccharides derived from Hypsizygus marmoreus on LPS in lungs [ 316 ].…”
Section: Pharmacological Actions Of Mushroommentioning
confidence: 99%
“…PEP showed anti-inflammatory activity in RAW 264.7 macrophages, inhibiting pro-inflammatory mediators’ production and inhibiting inducible nitric oxide synthase expression, showing its potency for anti-inflammatory activity in the colon [ 315 ]. Liu et al reported the action of polysaccharides derived from Hypsizygus marmoreus on LPS in lungs [ 316 ].…”
Section: Pharmacological Actions Of Mushroommentioning
confidence: 99%